2020
DOI: 10.1001/jamanetworkopen.2020.1934
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Improving Basic Preventive Measures in the Perioperative Arena on Staphylococcus aureus Transmission and Surgical Site Infections

Abstract: IMPORTANCE Surgical site infections increase patient morbidity and health care costs. The Centers for Disease Control and Prevention emphasize improved basic preventive measures to reduce bacterial transmission and infections among patients undergoing surgery. OBJECTIVE To assess whether improved basic preventive measures can reduce perioperative Staphylococcus aureus transmission and surgical site infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
98
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(101 citation statements)
references
References 28 publications
(148 reference statements)
1
98
2
Order By: Relevance
“…Meticulous intravascular catheter disinfection contributes to an overall reduction in SSIs [161]. Several studies have demonstrated the importance of regional anesthesia for the success of TJA at least in terms of complication spectrum/rate [162,163].…”
Section: Intraoperative Care For Tja Patientsmentioning
confidence: 99%
“…Meticulous intravascular catheter disinfection contributes to an overall reduction in SSIs [161]. Several studies have demonstrated the importance of regional anesthesia for the success of TJA at least in terms of complication spectrum/rate [162,163].…”
Section: Intraoperative Care For Tja Patientsmentioning
confidence: 99%
“…During anesthesia, bacterial and viral contamination of the anesthesia workspace routinely occurs, largely due to activities of the anesthesiologist and/or nurse anesthetist caring for the patient throughout the case [1,[37][38][39][40]. Multiple steps can be followed to mitigate this risk, as follows.…”
Section: Ambulatory Surgery Without Aerosol Production Without Genermentioning
confidence: 99%
“…(f) Double glove before touching the patient's nose/mouth and remove the outer glove following contact (e.g., placement of a nasal cannula) [54][55][56]. (g) After patient positioning, wipe down equipment and high-touch surfaces with disinfection wipes that contain a quaternary ammonium compound and alcohol [40,49,[56][57][58][59]. (h) Provide data feedback by surveillance of Enterococcus, Staphylococcus aureus, Klebsiella, Acinetobacter, Pseudomonas, and Enterobacter spp.…”
Section: Ambulatory Surgery Without Aerosol Production Without Genermentioning
confidence: 99%
“…The study by Loftus et al 1 is an important addition to the literature supporting bundled infection prevention interventions to reduce the burden of surgical site infections (SSIs). The authors prospectively randomized patients undergoing a heterogeneous mix of surgical procedures to receive a standardized perioperative infection prevention bundle vs existing standard of care and followed patients for 60 days.…”
mentioning
confidence: 99%
“…What was the cost needed to prevent an infection? What is the value added by this bundled intervention designed to reduce the pathogen reservoir compared with existing Centers for Disease Control and Prevention recommendations 3 that target perioperative antibiotic administration and host optimization?Demonstrating a reduction in transmission events and infections was important, but Loftus et al1…”
mentioning
confidence: 99%